The Efficacy of Feed Restriction Program on Broiler Production: A Review: - Hamdeen Yahia Dawood (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Poultry often intake energy to meet their energy needs, which is associated with both more fat and protein deposition, which is also conditioned by the presence of adequate other nutritional nutrients. The most significant supplement in creature sustenance or diets is protein, with exceptional thought given to the proportion among energy and protein in consumes less calories (energy: protein ratio EPR). This implies that a specific protein level relates with the fundamental measure of energy in the eating regimen. The article evaluated the manipulation of energy to protein ratio and its effect on broiler performance and carcass lipid profile. The author’s methodology depends on analyzing and comparing other scientists’ studies and work to evaluate the impact of protein-to-energy ratio on broiler performance and carcass fat deposition and found that high-energy or high-protein diets and widening the energy-to-protein ratio significantly increased fat deposition. Also, a low-energy diet increased broiler total cholesterol.